1967
DOI: 10.1001/archneur.1967.00470200105010
|View full text |Cite
|
Sign up to set email alerts
|

Precapillary Arteriovenous Anastomoses

Abstract: PRECAPILLARY arteriovenous anastomoses are a normal part of the microcirculatory bed of skin, muscle, lung, heart, intestine, liver, spleen, kidney, ear, and eye.1,2 These have been labeled "preferential channels"3 or "throughfare channels" by Chambers and Zweifach.4 Whether similar anastomoses occur in the brain parenchyma has been a subject of debate. Rowbotham and Little5-9 observed precapillary arteriovenous anastomoses in the pial circulatory system but not in the brain parenchyma of man, while Pfeifer10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
4

Year Published

1967
1967
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 22 publications
1
31
4
Order By: Relevance
“…Although both precapillary arteriolar-to-venous (5, 27) and arteriolar-to-arteriolar shunts (27,31) have been reported in brains of premature babies, our investigation failed to identify these anatomical structures in all specimens except one. We conclude that fetal brains exhibit a circulatory pattern that …”
Section: Anstrom Et Alcontrasting
confidence: 62%
See 1 more Smart Citation
“…Although both precapillary arteriolar-to-venous (5, 27) and arteriolar-to-arteriolar shunts (27,31) have been reported in brains of premature babies, our investigation failed to identify these anatomical structures in all specimens except one. We conclude that fetal brains exhibit a circulatory pattern that …”
Section: Anstrom Et Alcontrasting
confidence: 62%
“…There is little evidence to support the view that brain arterioles and veins are connected by shunts. The primary source of support for arteriolar-to-venous shunts is Hasegawa et al (27), who reported finding large numbers of shunts, or "thoroughfare channels," in thick slices of both dog and human brain tissue stained to reveal arterioles, capillaries, and veins. However, Saunders and Bell (28), Duvernoy et al (17), and Moody et al (12) suggest that these shunts were misdiagnosed and that the structures reported as shunts were actually crossing vessels rather than joining vessels.…”
Section: Anstrom Et Almentioning
confidence: 99%
“…Anatomical arteriovenous shunts below the cortical surface, 64 if present, also may shift considerable volumes of blood in the face of surface microvascular spasm. The overall effect of physiological and anatomical shunts resulting from hemorrhagic or traumatic microvascular spasm would be for blood to be flowing around, through, and past an area of cerebrum, bypassing the capillary beds, and precluding tissue exchange of metabolites.…”
Section: -63mentioning
confidence: 99%
“…The existence of precapillary sphincters is generally accepted, and there is experimental anatomical evidence for the presence of small (15 to 25/x) arteriovenous thoroughfare channels, 15 -10 which might account for some of the rapid flow rates obtained, particularly those from three compartment curves. These rapid flow rates also might be because an electrode was near an artery (particularly with the large electrodes).…”
Section: Figurementioning
confidence: 99%